Microstructure and mechanical properties of ultrasonically welded aluminum to Zn–Mg–Al coated and uncoated mild steels - Godwin Kwame Ahiale; Hamid Reza Javadinejad; Mokoung Lee; HyunCheol Kim; Jeoung Han Kim (Journal of Materials Research and Technology, 2024)
The gaining popularity of aluminum alloys in the automotive industry demand the development of energy efficient joining methods of Al with other metals such as steel. Among such joining methods, ultrasonic welding is advantageous because it is cost effective and prevents metallurgical defects because of the low welding energy involved. This study evaluates the microstructural changes and mechanical properties of dissimilar ultrasonic welding of Al to Zn–Mg–Al-coated and uncoated mild steels. Various intermetallic compounds (IMCs), such as FeAl3, and Fe2Al5 with different thicknesses and morphologies were observed at the joint interfaces. The Al-to-Zn-Mg-Al-coated steel exhibited mechanical properties that are superior to those of Al-to-uncoated mild steel. The results are discussed in terms of microstructure evolution, joint characteristics, and interfacial reactions in the welds. This study contributes to the understanding of the mechanisms behind strong ultrasonic welding of dissimilar metals.